Importance of testosterone and cortisol in prediabetic and diabetic male patients in Diyala Governorate (Iraq) - Arif, A. I.; Rmaidh, A. Y.; Qaddoori, H. T.; Mohammad, S. Q. (Regulatory Mechanisms in Biosystems, 2025)
This study aimed to investigate the predictive role of biochemical and hormonal indicators in screening patients with pr e diabet es and diabet es . This research was carried out in Diyala province from March – June 2024. 60 samples were collected from patients (30 prediabetic and 30 diabetic) who visit ed the consultation clinic at Baq a b i Teaching Hospital. 30 samples were collected from healthy subjects as a control group. All indicators were quantified by a Biorex machine. The r esults show diffe r ences in glucose with prediabetic and diabetic individuals mostly within the groups 31 – 50 and >50 . Prediabetic and diabetic patients were often overweight or obese. They had higher levels of FBS, HbA1C, and cortisol than control, while testosterone levels were lower. The ROC curve indicated that FBS and HbA1C were more sensitive and specific than cortisol and testost e rone for predicting prediabetes and diabetes. Cortisol was more effective than testosterone for prediabetes screening, while testosterone was better for diabetes. In conclusion, elevated indicators (except testosterone) we re observed compared to normal glucose levels. HbA1C and FBS we re most effective for screening. Cortisol wa s better for prediabetic screening, while testo s terone wa s better for diabetes. BMI ha d no significant effect on indicators in diabetics.